Persepsi Dan Partisipasi Masyarakat Desa Giritirto Kecamatan Purwosari Gunung Kidul Terhadap Kegiatan Program Posyandu - Puji Lestari * (Dimensia: Jurnal Kajian Sosiologi, 2007)
The objective of this research is to understand the development of activities, participations, and perception on POSYANDU program and to understand the correlation between perception and participation of all the society according to social economy and social culture conditions The method of descriptive qualitative is used in this research for the reason that this method is able to convey and to uncover a lot of information with more in accuracy and meaning. Despite bringing into play the qualitative method, the quantitative method is not being put aside as well. From every object observed, a tendency, patterned ways of think, irregularity, and behavioral appearance and its integration as in genetic study of case will be seen. Genetic study of case is being used as a strategy of research since the issues and focus of this research have been determined before in the research proposal prior to field research. Hence, research strategy afterward is included as the embedded of research study of case. This research then wraps up and comes into the conclusion that POSYANDU program in the village of Giri Tirto is consistently implemented which has developed into society’s tradition. The varieties of society’s participations in POSYANDU program are limited to their comprehension and understanding about what POSYANDU program is. The most participating party in this program is the families who have a baby (less than five years-old baby), while the worker’s contribution is to give service to baby growth. The role of the elite figures and village peripherals are very limited in giving advice for POSYANDU Activities. The character of a simple life is also expressed in simple behaviors in daily life. Keywords: Participation, POSYANDU, Perception, Society, Program.